Awareness and Adoption of Climate Change Adaptation Strategies among Coastal Tourism Stakeholders in the Blue Economy Framework - Ayuba Kaluri (Journal of Energy Technology and Environment, 2024)
The study assesses the Awareness and Adoption of Climate Change Adaptation Strategy among Coastal Tourism Stakeholders in the Blue Economy Framework. The target population consists of stakeholders in the coastal tourism sector, including tourism operators, community members that are involved in tourism activities, local government officials and the representatives of environmental or conservation organizations. A stratified random sampling technique was used for the selection of the respondents. The sample size were 300 respondents. Structured questionnaire was used for the collection of data. Descriptive statistics of mean and standard deviation was used to answer the research questions while the Inferential Statistics of Chi-square and Parson Product Moment Correlation Coefficient were used to test the hypotheses at 0.05 level of significance. The results revealed that there is a significant relationship between level of awareness on climate changes, it’s impacts and the adoption of climate changes adaptation strategies among coastal tourism stakeholders and there is a significant awareness of climate change and adaptation strategies among coastal tourism stakeholders. The researcher recommended that: unique climatic issues that coastal regions face, governments, environmental groups, and tourism associations should create and carry out awareness programs. Social media, community gatherings, and seminars are all efficient ways to reach a large audience. Stakeholders' comprehension of climate risks and adaptation strategies can be strengthened through training sessions, educational seminars, and digital learning materials centered on regional climate.
Keywords: Blue Economy; Climate Change; Environmental Conservation; and Coastal .